Country Partnership Framework for the Republic of Iraq for the Period FY2022-FY2026 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2021)
Iraq is at a crossroads. The Iraqi government struggles to navigate internal as well as regional security challenges. Despite the current uncertain circumstances, the Country Partnership Framework (CPF) provides a suitable country engagement instrument to support Iraq’s progress and builds off of longstanding World Bank Group (WBG) engagement and partnership with Iraq, including in the period since the last CPF and Performance Learning Review (PLR). This CPF is organized under two pillars and supported by foundational elements – (i) improved governance, public service delivery, and private sector participation, and (ii) strengthened human capital.